2019
DOI: 10.3233/jhd-190366
|View full text |Cite
|
Sign up to set email alerts
|

Glycation in Huntington’s Disease: A Possible Modifier and Target for Intervention

Abstract: Glycation is the non-enzymatic reaction between reactive dicarbonyls and amino groups, and gives rise to a variety of different reaction products known as advanced glycation end products (AGEs). Accumulation of AGEs on proteins is inevitable, and is associated with the aging process. Importantly, glycation is highly relevant in diabetic patients that experience periods of hyperglycemia. AGEs also play an important role in neurodegenerative diseases including Alzheimer's (AD) and Parkinson's disease (PD). Hunti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 176 publications
(196 reference statements)
0
11
0
Order By: Relevance
“…Given inflammation is considered a pathological hallmark of neurodegeneration, it is important to consider what affect this inflammatory response could have on adaptive immunity, particularly given adaptive immunity also serves to support the function of innate immunity and the dialogue between the two is critical and constant. In support of neurodegeneration driving these immune processes, variation in CSF glycan expression has been detected in multiple neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease, Huntington’s disease and amyotrophic lateral sclerosis ( 46 , 50 56 ). Our data adds bvFTD to this list of CNS diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Given inflammation is considered a pathological hallmark of neurodegeneration, it is important to consider what affect this inflammatory response could have on adaptive immunity, particularly given adaptive immunity also serves to support the function of innate immunity and the dialogue between the two is critical and constant. In support of neurodegeneration driving these immune processes, variation in CSF glycan expression has been detected in multiple neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease, Huntington’s disease and amyotrophic lateral sclerosis ( 46 , 50 56 ). Our data adds bvFTD to this list of CNS diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies showed that the AGEs and the advanced lipoxidation end products (ALEs) are involved in the development and progression of chronic degenerative diseases, including diabetes [28][29][30], cardiovascular diseases [29,31,32], neurological disorder [33,34], some types of cancer [35,36], and all those pathologies in which the mechanisms of oxidative stress are involved, as well as the senescence processes [33].…”
Section: Age's Biochemistrymentioning
confidence: 99%
“…The formation of AGEs by the Maillard reaction gained prominence in human health research during the 1950s, after the discovery of glycated hemoglobin under physiological conditions and its reported correlation with glycemic levels in diabetic patients [ 63 ]. The glycation of cellular proteins has a negative effect on cell and tissue function, molecular aging, and chronic disease development [ 64 , 65 ]. In addition to their endogenous occurrence, AGEs are also formed during the thermal processing of foods, significantly increasing humans’ exposure to dietary AGEs (dAGEs).…”
Section: High-age Diets and Clgi Initiation In Murine Modelsmentioning
confidence: 99%
“…In addition to their endogenous occurrence, AGEs are also formed during the thermal processing of foods, significantly increasing humans’ exposure to dietary AGEs (dAGEs). Food-borne AGEs are part of a heterogeneous group of chemically stable molecules resulting from the Maillard reaction, some of which are implicated in benignly improving flavors, aromas, and browning, while others are thought to be involved in adverse health effects (e.g., chronic inflammation, degenerative diseases, aging, insulin resistance) [ 64 , 65 ].…”
Section: High-age Diets and Clgi Initiation In Murine Modelsmentioning
confidence: 99%